2011
DOI: 10.1029/2010wr009889
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation suppression from water reservoirs: Efficiency considerations of partial covers

Abstract: [1] Reservoirs enhance availability and temporal stability of water resources, however, water losses due to evaporation may significantly reduce their operational efficiency. Studies have evaluated the efficacy of various types of chemical or physical evaporation barriers often on a qualitative basis. Certain design and maintenance advantages are offered by self-assembling modular floating covers especially for large reservoir surfaces. Evidence suggests that evaporation suppression efficiency of these floatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
2
51
0
1
Order By: Relevance
“…These nonlinearities are attributed to vapor diffusion 10 from water gaps across air viscous boundary layer (Schlünder, 1988;Shahraeeni et al, 2012; and potential feedback on the gap temperature (Aminzadeh and Or, 2013). The combined effects of gap size, spacing and thickness of the air boundary layer (Shahraeeni et al, 2012) support laboratory experimental results of Assouline et al (2011) that have shown higher evaporation rates from small water gaps (per unit gap area) relative to evaporation rates from larger gaps (with similar 15 uncovered surface fraction). These nonlinear relationships and additional energetic constraints must be considered in design and deployment of evaporation suppression floating covers.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…These nonlinearities are attributed to vapor diffusion 10 from water gaps across air viscous boundary layer (Schlünder, 1988;Shahraeeni et al, 2012; and potential feedback on the gap temperature (Aminzadeh and Or, 2013). The combined effects of gap size, spacing and thickness of the air boundary layer (Shahraeeni et al, 2012) support laboratory experimental results of Assouline et al (2011) that have shown higher evaporation rates from small water gaps (per unit gap area) relative to evaporation rates from larger gaps (with similar 15 uncovered surface fraction). These nonlinear relationships and additional energetic constraints must be considered in design and deployment of evaporation suppression floating covers.…”
Section: Introductionsupporting
confidence: 70%
“…where w f and c f are the areal fractions of free and covered surface, respectively ( 1 comparison with the thickness of viscous sublayer (Assouline et al, 2011). Hence, the reduction of vapor diffusion resistance from individual gaps due to the formation of three-dimensional vapor shells (governed by the combined effect of gap size g a , boundary layer thickness and lateral spacing) would enhance vapor diffusion and result in values of ϕ 1 ≥ (Schlünder, 1988;Shahraeeni et al, 2012):…”
Section: The Energy Balance Of Partially Covered Reservoirsmentioning
confidence: 99%
See 3 more Smart Citations